No Ordinary Optimization Problem

Calculus Level 3

If a , b , c > 0 a, b, c>0 and a + b + c = 1 a+b+c=1 , the minimum value of ( a + 1 a ) 10 + ( b + 1 b ) 10 + ( c + 1 c ) 10 (a+\frac{1}{a})^{10}+(b+\frac{1}{b})^{10}+(c+\frac{1}{c})^{10} can be expressed as 1 0 d 3 e \frac{10^{d}}{3^{e}} where d d and e e are positive integers. Find d + e d+e


The answer is 19.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Jakub Šafin
Nov 26, 2014

The restriction and minimized expression are of special forms k = 1 3 g ( x k ) = 0 , k = 1 3 f ( x k ) = m i n . \sum_{k=1}^3{g(x_k)}=0,\\\sum_{k=1}^3{f(x_k)}=\mathrm{min.}

with g ( x ) 0 g(x) \neq 0 . In this case, the theorem of Lagrange multipliers takes a simple form λ = f ( x k ) g ( x k ) = c o n s t . \lambda=\frac{f'(x_k)}{g'(x_k)}=\mathrm{const.}

After calculating λ ( x ) \lambda(x) and its first derivative, we can see that λ ( x ) = 10 ( x + 1 x ) 9 ( 1 1 x 2 ) , λ ( x ) = 90 ( x + 1 x ) 8 ( 1 1 x 2 ) 2 + 20 ( x + 1 x ) 9 1 x 3 , \lambda(x)=10\left(x+\frac{1}{x}\right)^9\left(1-\frac{1}{x^2}\right),\\ \lambda'(x)=90\left(x+\frac{1}{x}\right)^8\left(1-\frac{1}{x^2}\right)^2+20\left(x+\frac{1}{x}\right)^9\frac{1}{x^3}, where λ ( x ) > 0 \lambda'(x) > 0 for x > 0 x > 0 , so the only way for λ ( x k ) \lambda(x_k) to be constant for all k k is for all x k x_k to be equal.

It follows that x k = a , b , c = 1 / 3 x_k=a,b,c=1/3 and the minimum of our expression is 1 0 10 / 3 9 10^{10}/3^9 .

Uma T V
Nov 22, 2014

AM of nth powers>=AM power n: Let R=(a+1/a)^10+(b+1/b)^10+(c+1/c)^10 R/3>=[{(a+1/a)+(b+1/b)+(c+1/c)}/3]^10 Also, using AM>=HM, we get: 1/a+1/b+1/c>=9 R/3>=[{a+b+c+1/a+1/b+1/c}/3]^10>=[{1+9}/3]^10=(10/3)^10 So, R>=(10^10)/(3^9)

James Wilson
Dec 6, 2017

I don't know how to justify this solution, but I set a + 1 a = b + 1 b = c + 1 c a+\frac{1}{a}=b+\frac{1}{b}=c+\frac{1}{c} , which implies a = b = c a=b=c . Perhaps some sort of curvature argument involving the AM-GM inequality will work?

Pietro Domingues
Nov 22, 2014

Using lagrange multipliers, we see that a=b=c. So a b and c must be 1/3.

Can you show the work and explain how to use Lagrange Multipliers?

Calvin Lin Staff - 6 years, 6 months ago
Nayanmoni Baishya
Nov 21, 2014

Take a=b=c=1/3

Why must that give us the minimum?

Calvin Lin Staff - 6 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...